2013
DOI: 10.3390/md11051693
|View full text |Cite
|
Sign up to set email alerts
|

“Head-to-Side-Chain” Cyclodepsipeptides of Marine Origin

Abstract: Since the late 1980s, a large number of depsipeptides that contain a new topography, referred to as “head-to-side-chain” cyclodepsipeptides, have been isolated and characterized. These peptides present a unique structural arrangement that comprises a macrocyclic region closed through an ester bond between the C-terminus and a β-hydroxyl group, and terminated with a polyketide moiety or a more simple branched aliphatic acid. This structural pattern, the presence of unique and complex residues, and relevant bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 129 publications
0
42
0
1
Order By: Relevance
“…The spectral data were identical to those of the natural product. 16,17) As it was reported that the dehydration of apratoxin A occurred in CDCl 3 , 5) we also observed the isomer of apratoxin A by LC/MS analysis after recording the NMR spectrum in CDCl 3 . We synthesized 34-epi apratoxin A (29) to confirm the structure of the isomer, because it might be a rotamer, although it was not likely observed (Chart 7).…”
Section: Total Synthesis Of Apratoxin a And In Vivo Evaluationmentioning
confidence: 62%
See 1 more Smart Citation
“…The spectral data were identical to those of the natural product. 16,17) As it was reported that the dehydration of apratoxin A occurred in CDCl 3 , 5) we also observed the isomer of apratoxin A by LC/MS analysis after recording the NMR spectrum in CDCl 3 . We synthesized 34-epi apratoxin A (29) to confirm the structure of the isomer, because it might be a rotamer, although it was not likely observed (Chart 7).…”
Section: Total Synthesis Of Apratoxin a And In Vivo Evaluationmentioning
confidence: 62%
“…[1][2][3] The cyclodepsipeptides contain a hydroxy acid that bears one or more chiral centers, and also often contain N-methylamino acids, which significantly increases the structural diversity of these compounds. The ester linkage between a hydroxy acid and an amino acid is also a unique structural feature.…”
Section: Introductionmentioning
confidence: 99%
“…A headto-side-chain peptide is a cyclic peptide in which the macrocyclization happens to occur between the C-terminus and a side chain. This b-branched framework, which characterizes all the members of this new class of non-ribosomal cyclodepsipeptides 5 , comprises the following: a 22-or a 25-membered macrolactone; the presence of complex and rare amino acids; a branching position occupied by a D-allo-b-hydroxy-a-amino acid acylated by the unique (2S,3S,4R)-3,4-dimethylglutamine (diMeGln) residue; and an N-terminus coupled to a saturated or unsaturated b-hydroxy acid. Examples of members of this family include callipeltin A 6 , papuamides 7,8 , neamphamides [9][10][11] , theopapuamides 12,13 , mirabamides 14,15 and homophymines 16,17 .…”
mentioning
confidence: 99%
“…B. die Rückgrat‐, Seitenkette‐Rückgrat‐ und Seitenkette‐Seitenkette‐Cyclisierung 42. 43 Erste Beispiele für makrocyclische Peptide als Kehrenmimetika wurden für Peptidliganden berichtet, deren Zielproteine membranassoziierte Rezeptoren sind. Auf diesem Gebiet haben Kessler und Mitarbeiter Pionierarbeit geleistet, indem sie eine Struktur‐Wirkungs‐Beziehung von Rückgrat‐cyclisierten Peptiden mithilfe von NMR‐Spektroskopie aufgestellt haben 44.…”
Section: Methodikunclassified